Genomic landscape of multiple Bowenʼs disease using whole‐exome sequencing. Issue 3 (19th September 2022) - Kim, Yoon‐Seob; Park, Gyeong Sin; Bang, Chul Hwan; Chung, Yeun‐Jun
Abstract: The genomic landscape of Bowen's disease (BD), with multiple manifestations, has not yet been determined. This study aimed to investigate the genomic alterations in multiple BD. We performed whole‐exome sequencing of BD lesions ( n  = 9) and matched germlines collected from three patients with multiple (≥3) BD to detect somatic and germline mutations. We found a median of 64 somatic mutations in each sample (range 20–267). UV‐signature mutations accounted for 64.9% (median, range 26.0%–82.1%) of point mutations. Putative driver mutations were found in five BDs ( RB1 p.R445*, ARID2 p.R274*, TP53 p.Y163D/p.Y205D/p.R342*, KMT2C p.R4549C) but not in the other four lesions. Somatic mutations were not shared between multiple BD lesions collected from the same patient, indicating a different clonal origin. We also found no known pathogenic germline mutations in cancer‐related genes. The mutational signature analysis revealed that UV signatures (SBS7a/7b) and age‐related signatures (SBS1/5) were the main active signatures. Copy number alterations (CNAs) were found in two BDs: one with extensive CNA regions (21.7% of the genome), including driver genes ( PIK3CA / SOX2 / TP63 and MYC gain, and CDKN2A loss), and the other with 1q gain. Our study revealed that multiple BD lesions harbor distinct genomic landscapes, suggesting that they have different risks of malignant progression.